As fronteiras do Brasil: fluxos comerciais transfronteiriços nas cidades conectadas por pontes binacionais - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The goal of this article is to analyze cross - border trade flows in a comparative way, with the purpose of studying the Brazilian cities located in the borders that have binational bridges and the countries to which they are connected through this infrastructure. Each border city has a different prominence within the exports and imports of basic, semi-manufactured and manufactured goods. This difference in trade flows is a reflection of the varied interests of the connected States, taking into account the quality of the infrastructures and binational agreements that can help optimize international trade. For the accomplishment of this study, a bibliographical research was done to understand the context of each city and for the analysis and reflections on this international trade were collected and tabulated official data of the Ministry of Industry, Foreign Trade and Services and used the resource of thematic cartography. It is possible to conclude that the Brazilian border cities that have the highest state attention for logistical, infrastructural and legal investments are also the ones that have the highest commercial flows, so Foz do Iguaçu (PR) has a high prominence in this area, besides the localized border cities in Rio Grande do Sul. In addition, it is the manufactured products that stand out in both exports and imports
Keywords: Comércio internacional; Pontes binacionais; Relações fronteiriças; CNPQ::CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL::RELACOES INTERNACIONAIS, BILATERAIS E MULTILATERAIS